Kajian Kapasitas Adaptasi Masyarakat Pesisir Pekalongan terhadap Kerentanan Banjir Rob - Hilma Qoniana Purifyningtyas; Holi Bina Wijaya (Department of Urban and Regional Planning, Diponegoro University, 2016)
Pekalongan City is a coastal city vulnerable to tidal flood. There are eight tidal flood prone villages including Pabean and Bandengan villages. Community adaptive capacity requires improvements to dealing with it. This study aimed to assess the adaptive capacity of the coastal communities in Pekalongan against the tidal flood vulnerability. The study employed quantitative method with scoring and descriptive statistical analyses for synthesizing the results. The adaptive capacity was assessed at the levels of individuals, communities and cities. It also measured physical, social, and economic aspects. The results showed that at the individual level the adaptive capacity level of communities in both villages was low. It was caused by the low ability of the communities to fixing their houses. It was also influenced by their education and income levels. At the community level, the level of adaptive capacity was determined by the ability of communities to improve infrastructure. It was also determined by the existence of the organization and their ability to raise funds. At this level, the level of adaptive capacity was moderate. At the city level, the government was able to adapt by providing technology and institution. The community needs to increase the adaptive capacity by improving the ability of the economyin addition tooptimizing the performance of government and non-government organizations.